Agrifood value chains are complex transaction-linked networks what does this mean for sampling methodology? - Ambler, Kate; de Brauw, Alan; Bloem, Jeffrey R.; Wagner, Julia (CGIAR Initiative on Rethinking Food Markets, 2024)
Agrifood value chains are an integral part of food systems, moving food from farms where it is produced to retailers where it is sold to consumers. Agrifood value chains can be quite simple—consumers can buy directly from farms at farmers’ markets, for example—or they can be quite complex, involving processing steps on multiple continents before products reach retailers. Yet research often sets aside these distinctions and depicts agrifood value chains as highly stylized and simple—typically as a simplified series of steps involving traders, aggregators, processors, and/or wholesalers between farms and retailers. The most common method for studying multiple intermediary actors within agrifood value chains—“stacked surveys” that randomly sample respondents within each of these steps—follows this simplified approach.